Empowering underachieving youths in producing videos on social media: a study on the effectiveness of the BE:GINOW Training Programme / Che Nooryohana Zulkifli ... [et al.] - Zulkifli, Che Nooryohana; Ab. Latif, Nur Afiqah; Desa, Melati; Raja Berahim, Raja Rosila; Abd. Hamid, Nurul Bazilah (Universiti Teknologi MARA, Perlis, 2024)
This study conducted a detailed analysis of how academically underachieving youth use technology and social media to create videos as part of a training programme called BE:GINOW. A mixed study design that combined a quantitative method using questionnaires and qualitative methods through interviews was used. The questionnaires were distributed through two phases: pre-BE:GINOW programme (Phase 1) and post-BE:GINOW programme (Phase 2), which intended to compare the videos produced by the participants before and after the programme. We also conducted two interview sessions to obtain feedback from external facilitators and participants on the effectiveness of the programme. The results show that BE:GINOW has successfully helped the participants produce more quality videos after eight months of participating in the programme. Respondents agreed that the post-programmed videos were better in terms of presentation structure, message delivery, language use and presentation style. The external facilitators and participants also confirmed the effectiveness of BE:GINOW in motivating and guiding the underachieving youth to improve their skills in the production of videos. It is envisaged that a programme like BE:GINOW will serve as a model for future technology-based training, acting as a catalyst for academic underachievers to expand their life skills and become active content creators.